Educational Robotics and Robot Creativity: An Interdisciplinary Dialogue - Gubenko, Alla; Kirsch, Christiane; Smilek, Jan Nicola; Lubart, Todd; Houssemand, Claude (Frontiers in Robotics and AI, 2021)
Recent studies suggest that educational robotics may have a positive effect on creativity. Authors claim that robotics in classrooms may be a promising new tool to address the creativity crisis in school. Although this line of research is up-and-coming, we often face a lack of theoretical development of the concept of creativity and the mechanisms involved. With few exceptions, authors do not discuss how exactly creativity is boosted and what cognitive components are promoted by the training. In this article, we will first provide an overview of existing research using educational robotics to foster creativity. We will use a confluence model of creativity to account for the positive effect of designing and coding robots on students' creative output. We will zoom on cognitive components of the process of constructing and programming robots and compare them with existing models of creative cognition. We will also address the question of the role of meta-reasoning and strategies in the creative process. We will finally discuss how the notion of creativity applies to robots themselves and present the distinguishing characteristics between human and robotic creativity. Ultimately, we argue that considering how robots and humans deal with novelty and solve open-ended tasks could help us to understand better some aspects of the essence of human creativity, although human creativity cannot be reduced to cognition.